THE SPACE OF THERMOMETRIC SIGNS IN THE PROBLEM OF MAMMARY GLANDS CANCER DIAGNOSIS - E. Mazepa; V. Dubovskaya (Современная наука и инновации)
This work is devoted to testing the hypothesis of homogeneity of modeling functions from temperatures constructed for each qualitative sign of cancer. The following results are obtained in the article. During the analysis of the results of determining homogeneity for each control class, it was revealed that the class "Healthy" and the class "Risk Group" are characterized by heterogeneity in most of the signs in the context of age, diameter of the mammary glands and the location of the survey. The signs of the class "Cancer" are characterized by homogeneity. The regularity of the inhomogeneity was not detected. The effect of a particular temperature measured at a particular point on the uniformity of the results was not revealed. The work is devoted to statistical verification of the homogeneity of samples offeature in the context of the age of the patients, the diameter of the mammary glands and the place of the examination.